(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Starting from the fact that it is not enough to just get rid of evil, but that the essence is to get away from the evil and get the evil away, and you can only do that when you start doing good, seemly to man as a temple of God - it becomes clear why and how an ethics of practical action, as is the case with St. Clement from Ohrid, grows into an ethics of spiritual shaping of the space and the people where they live. That St. Clement manages this, there is a proof in the case of St. Naum, so it should come as no surprise that in addition to being proclaimed a saint, he is more often called a "miraculous". One can become a "miraculous" when a certain group declares certain "healings" as a miracle of God, or when, understanding the ethics of his teachers Cyril and Methodius, but above all Clement’s, they become the starting point for creating a space in which man will come up to what the man is doing – a spiritual space in which he will find himself opening up to the Spirit. At the same time, without violating the identity of God, monastic or canonical, and opening space for building churches the walls of which will give space for anticipatory commentary on the world, but also space for those who will enter them by looking at the frescoes, the icons, listening to the word of God, come to themselves as a temple of God, but universally ethically constructed – is the result that confirms this ethics of miraculousness, the ethics of the people’s spirit. Such an ethical qualification of Naum’s life result is also the subject of analysis of this text.